Pengaruh Servant Leadership terhadap Keterikatan Pegawai dengan Kepuasan Kerja sebagai Variabel Mediasi di Dinas Pekerjaan Umum dan Perumahan Rakyat Provinsi Jambi - Ovalina Citra Clara Manalu; Hendriyaldi Hendriyaldi; Feny Tialonawarmi (Fakultas Ekonomi & Bisnis, Univ, 2026)
This study was designed to examine the influence of servant leadership on employee engagement, while also analyzing its relationship with job satisfaction and how job satisfaction influences overall employee engagement. The focus of this study also included an analysis of the role of job satisfaction as a mediating variable at the Jambi Province Public Works and Housing Agency (PUPR). The researchers employed a quantitative approach by distributing a Likert-scale questionnaire to a sample of 59 employees. Prior to drawing conclusions, the primary data was validated through validity and reliability tests, then statistically analyzed using SmartPLS 4.0 software to test each proposed hypothesis. Field observations indicated that the implementation of servant leadership was in the good category, accompanied by high levels of employee engagement and a satisfactory job satisfaction index. Empirically, this study confirmed that servant leadership has a positive and significant influence on both employee engagement and job satisfaction. Furthermore, job satisfaction was found to act as a mediating variable linking the influence of servant leadership on employee engagement. Referring to these findings, it is recommended that management prioritize aspects of well-being, competency development, and recognition of staff contributions. In addition, creating a supportive and collaborative organizational climate is essential to maintaining stable employee satisfaction and engagement.